2001
DOI: 10.1002/j.2325-8012.2001.tb00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Maternity Leave Induce Births?

Abstract: Alleviating the tension between the conflicting responsibilities women may face as mothers and as workers is a topic of current policy interest. Expansion of guaranteed maternity leave to all employed women in the United States is suggested as one possible “family‐friendly” solution. Controversy surrounding the issue of increased maternity leave centers around the potential cost to firms of widespread access to leave. One specific concern is that the availability of maternity leave will actually increase birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Parental leave beneficiaries were 3.63 times more likely to consider planning childbirth, which is consistent with the findings of previous studies that reported a positive relationship between family policy and parturition [ 22 , 23 ]. It has been confirmed that the parental leave system positively affects women’s view of marriage [ 24 ] and maternal health [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Parental leave beneficiaries were 3.63 times more likely to consider planning childbirth, which is consistent with the findings of previous studies that reported a positive relationship between family policy and parturition [ 22 , 23 ]. It has been confirmed that the parental leave system positively affects women’s view of marriage [ 24 ] and maternal health [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Some studies link paid and job-protected maternity benefits with positive effects on fertility, such as in Austria (Lalive & Zweimüller, 2009) and Germany (Raute, 2019). In contrast, paid maternity leave did little to encourage fertility in Norway (Dahl et al, 2016) and there is mixed evidence in the case of the US (Averett & Whittington, 2001;Flores et al, 2023;Golightly & Meyerhofer, 2022;Olivetti & Petrongolo, 2017;Pihl & Basso, 2019;Rossin-Slater et al, 2012). See Olivetti and Perengolo (2017) for a full review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The provision of maternity leave has also received attention for its potential fertility effects as it can lower the cost of childbearing when leave is available. Early research demonstrated a link between maternity leave and fertility (Averett and Whittington, 2001). More recent work has used the adoption of the Family and Medical Leave Act in the US in 1993 to identify the effect of leave on fertility and has found positive effects (Cannioner, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%